Proses Pemilihan Kepala Daerah Secara Langsung yang Berdampak pada Perilaku Masyarakat dalam Rangka Pemenuhan Hak Berpolitik Warga Negara di Provinsi Sumatera Utara - Tony Yuri Rahmanto (Jurnal HAM, 2015)
Direct local elections is an illustration form of the democratic process that is realized by the government's seriousness implemented at all levels of government. Implementation of the local elections have a purpose to carry out the implementation of a democratic system at the local level which is an extension of the central government, furthermore also a moment for the community to voicing their political rights as citizens. In practice, direct election conducted in some areas not yet in spite of the existence of violations to cause conflict between the members. The problem is how to practice the local elections directly in the province of North Sumatra; How is the behavior of the people of North Sumatra to direct the election process have been implemented. Methods This study used a qualitative approach which is descriptive study. Then conducted a qualitative analysis of the substance, the context, and the relationship between the perpetrators of the campaign with an audience from the aspect of human rights. Based on field data, direct election practices still use transactional practice, discrimination against particular groups, the lack of availability of facilities for the group of disabled tools, election fraud, organizers are still in favor of one candidate, the high cost elections, prone to horizontal conflict as a result of people's behavior, and the function of political education are not optimal.